Improving user QoS by relaxing resource reservation policy in high-performance grid environments. (1st January 2013) - Xiao, Peng; Han, Ning
Advance reservation is to provide end-to-end quality-of-service (QoS). However, excessively using advance reservation will lead to lower utilisation and higher rejection. To mitigate the negative effects of advance reservation, a temporal-spatial relaxing technique is proposed in this paper. It is based on an observation that applications tend to overestimate their reservation durations. The proposed technique is completely compatible with the classical reservation mechanism, which means it can be conveniently applied in most practical systems. The experimental results show that the relaxed reservation technique can achieve higher resource utilisation and lower rejection rate comparing with other techniques. Also, it shows better robustness when the grid systems is in the presence of high rate of reservation requests.